Appropriate baseline laboratory testing following ACEI or ARB initiation by Medicare FFS beneficiaries. Issue 9 (15th March 2016) - Maciejewski, Matthew L.; Hammill, Bradley G.; Qualls, Laura G.; Hastings, Susan N.; Wang, Virginia; Curtis, Lesley H.
Abstract: Background: Laboratory testing to identify contraindications and adverse drug reactions is important for safety of patients initiating angiotensin‐converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs). Rates and predictors of appropriate testing among Medicare fee‐for‐service beneficiaries are unknown. Purpose: The study's purpose was to examine baseline laboratory testing rates, identify predictors of suboptimal testing, and assess the prevalence of abnormal creatinine and potassium among beneficiaries initiating ACE inhibitors or ARBs. Design and Subjects: Retrospective cohort of 101 376 fee‐for‐service beneficiaries from 10 eastern US states in 1 July to 30 November 2011. Main Measures: Appropriate monitoring for serum creatinine or serum potassium was defined as evidence of an outpatient claim within 180 days before or 14 days after the index prescription fill date. Key Results: Thirty‐eight percent of beneficiaries were men, 78% were White race, 26% had prevalent heart failure, and 89% had prevalent hypertension. Rates of appropriate baseline laboratory testing were 82.7% for potassium, 83.2% for creatinine, and 82.6% for both potassium and creatinine 180 days prior to initiation. In logistic regression, men (odds ratio [OR] = 1.15, 95% confidence interval [CI]: 1.11, 1.19), African‐Americans (OR = 1.26, 95%CI: 1.20, 1.32), and beneficiaries with Alzheimer's disease and related disorders (OR = 1.22, 95%CI: 1.15, 1.28) or stroke (OR = 1.34, 95%CI: 1.26, 1.43) were more likely to experience suboptimal testing. At baseline, hyperkalemia was relatively uncommon (5.8%), and elevated creatinine values were rare (1.4%). Conclusions: Appropriate monitoring could be improved for African‐American beneficiaries and beneficiaries with a history of stroke or Alzheimer's disease and related disorders initiating ACE inhibitors or ARBs. Copyright © 2016 John Wiley & Sons, Ltd.